Adesão nos doentes transplantados - Telles-Correia, Diogo (2007)
There is a lot evidence about the importance adherence in the transplantated patients. Many theoretical models that can me used to predict adherence, the more important are: the communication model of compliance (Ley), the health belief model (Rosenstock, Becker), and the autoregulation model (Leventhal). The authors explore these models and sugest the one wich is more useful in transplantated patients. It is not possible to classify adherence in a monodimensional way, therefore it is useful to consider several catacteristics like timing (early, late, continuous), frequency (occasional, intermittent, persistant, complete), origin (accidental, invulnerable, decisive) and diagnostic certaincy (definite, probable, possible, unlikely). There are many ways to mesure adherence. These can be classified in direct methods (assays of drug concentrations, use of markers incorporated into pills, direct observation of pill taking) and indirect methods(patient self-reports, compliance ratings by doctors). The authors describe the various methods and suggest the ones that best suite transplantated patients. The non-adherence in transplantated patients is very common, it's medium prevalence is 25,28%, and can be influenced by many factors: demographic (age, civil state, sex, race, social/economic status), psychiatric and psychologic (depression, personality disorders, mental retardation, alcoholism, health/disease beliefs, locus control), and others (medication costs, pervious transplant).